2001
DOI: 10.1128/jvi.75.17.8268-8282.2001
|View full text |Cite
|
Sign up to set email alerts
|

Morbillivirus Infection of the Mouse Central Nervous System Induces Region-Specific Upregulation of MMPs and TIMPs Correlated to Inflammatory Cytokine Expression

Abstract: Viral infection of the central nervous system (CNS) can result in perturbation of cell-to-cell communication involving the extracellular matrix (ECM). ECM integrity is maintained by a dynamic balance between the synthesis and proteolysis of its components, mainly as a result of the action of matrix metalloproteinases (MMPs) and the tissue inhibitors of metalloproteinases (TIMPs). An MMP/TIMP imbalance may be critical in triggering neurological disorders, in particular in virally induced neural disorders. In th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
42
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 48 publications
(46 citation statements)
references
References 65 publications
(85 reference statements)
4
42
0
Order By: Relevance
“…In several infection models, the infiltration of activated T-lymphocytes into the brain is a wellcharacterized parameter linked to the development of encephalitis and neurodegeneration (Irani and Griffin, 1991;Khuth et al, 2001;Marten et al, 2003). A priming process initiated by a low number of infiltrating encephalitogenic T-lymphocytes could set the stage for a second greater wave of invading effector cells, as observed in multiple sclerosis patients and associated animal models (Engelhardt and Ransohoff, 2005;Norman and Hickey, 2005).…”
Section: -Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In several infection models, the infiltration of activated T-lymphocytes into the brain is a wellcharacterized parameter linked to the development of encephalitis and neurodegeneration (Irani and Griffin, 1991;Khuth et al, 2001;Marten et al, 2003). A priming process initiated by a low number of infiltrating encephalitogenic T-lymphocytes could set the stage for a second greater wave of invading effector cells, as observed in multiple sclerosis patients and associated animal models (Engelhardt and Ransohoff, 2005;Norman and Hickey, 2005).…”
Section: -Discussionmentioning
confidence: 99%
“…Such a cytoskeletal reconfiguration requires a complex and still not completely defined array of intracellular signaling pathways implicating second messengers, several kinases and Rho family small GTPases (del Pozo et al, 1999; 5 reaction with the infiltration of T lymphocytes, the expression of the cytokines TNF, IL6, IFN and IL-4 associated with the disruption of the tissue inhibitor of the metalloprotease TIMP/ metalloprotease MMP balance (Benscsik et al, 1996;Khuth et al, 2001) capable of modifying vascular permeability.…”
Section: -Introductionmentioning
confidence: 99%
“…In the cortex expression of TIMP-2, mRNA is observed predominantly in neurons [23,25]. Notably, TIMP-2 expression appears to be neither upregulated by neuronal depolarization nor by pathological conditions that activate TIMP-1 [23,31,32]. TIMP-3 is expressed at the lowest level in the adult rat brain [21], although its mRNA has been found in the cortex [33], cerebellum [17], thalamus, olfactory bulb [22], and brain stem [18].…”
Section: Timps In the Brainmentioning
confidence: 99%
“…It is thus interesting that MMP-2 is expressed at a much higher level during postnatal cortical development than in the adult neocortex (Dzwonek et al, unpublished). Inducible expression of MMP-2 in glia has also been noted following brain ischemia [20,42], kainate (KA) treatment as well as traumatic and viral brain injury [32,37,40,[47][48][49]. Interestingly, Asahi et al [50] showed that MMP-2 gene knockout in mice has no effect on brain injury after permanent and transient focal ischemia.…”
Section: Mmps In the Brainmentioning
confidence: 99%
See 1 more Smart Citation